Compartive Analysis of Mathematics Education Among Selected Southeast Asian Nations - Balderas, Melfred T.; Leones, Christy M.; Jonson, Angel May M.; Reyes, Tehrose Trizsha R. Delos; Galero, David Nicholas G.; Callaman, Roar (Universitas Muhammadiyah Surakarta, 2026)
The aim of this research was to explore the significant differences in content structure, pedagogical strategies, and evaluation processes in the mathematics curricula of selected Southeast Asian nations to ensure more responsive and effective curriculum development. The research was conducted through a comparative qualitative research method with a reliance on the systematic literature review as the most appropriate research method. The research was carried out exclusively through systematically identified and screened secondary sources, including peer-reviewed journal articles, international assessment reports and, curriculum frameworks to ensure methodological rigor, transparency, credibility, and consistency. The findings reveal significant differences in the structure, delivery, and evaluation processes in the mathematics curricula in Southeast Asia. The findings show that Singapore has a highly coherent curriculum with significant conceptual depth in its curriculum, with more focus on mastering and progressing to advanced levels of mathematical thinking. In contrast, the Philippines, Cambodia, Indonesia, and Brunei have more focus on mastering basic skills with contextual learning, with less systematic coverage of advanced levels of thinking in mathematics. The pedagogical strategies employed in the region range from highly structured mastery learning to student-centered and contextualized learning strategies. The evaluation processes in the region range from formative evaluation to mastery learning to more summative evaluation processes. The findings show that highly coherent, rich, and aligned curricula are critical in providing highly effective mathematics education in Southeast Asia.